# Proof of integral rule for Reciprocal of difference of squares

The integral rule for multiplicative inverse of difference of squares is used as a formula in integral calculus. It can be derived in mathematically by the indefinite integration.

$\displaystyle \int{\dfrac{1}{x^2-a^2}\,}dx$

### Factorize the square of difference

As per the difference of squares formula, the difference of squares of two terms can be factored mathematically.

$\implies$ $\displaystyle \int{\dfrac{1}{x^2-a^2}\,}dx$ $\,=\,$ $\displaystyle \int{\dfrac{1}{(x+a)(x-a)}\,}dx$

### Decompose the Rational Algebraic function

The function in rational form represents a rational expression that consists of non-repeated linear factors in the denominator. It can be decomposed as the sum of two partial fractions.

$\implies$ $\displaystyle \int{\dfrac{1}{(x+a)(x-a)}\,}dx$ $\,=\,$ $\displaystyle \int{\Bigg(\dfrac{A}{x+a}+\dfrac{B}{x-a}\Bigg)\,}dx$

Substitute $x = -a$, then $A$ $\,=\,$ $\dfrac{1}{-a-a}$ $\,=\,$ $\dfrac{1}{-2a}$ $\,=\,$ $-\dfrac{1}{2a}$

Substitute $x = a$, then $B$ $\,=\,$ $\dfrac{1}{a+a}$ $\,=\,$ $\dfrac{1}{2a}$

Now, replace the values of constants $A$ and $B$ in the expression, which consists of partial fractions.

$\implies$ $\displaystyle \int{\Bigg(\dfrac{A}{x+a}+\dfrac{B}{x-a}\Bigg)\,}dx$ $\,=\,$ $\displaystyle \int{\Bigg(\dfrac{\Big(-\dfrac{1}{2a}\Big)}{x+a}+\dfrac{\Big(\dfrac{1}{2a}\Big)}{x-a}\Bigg)\,}dx$

### Simplify the Algebraic rational expression

Now, simplify the algebraic expression in the rational form for evaluating the indefinite integration.

$=\,\,\,$ $\displaystyle \int{\Bigg(\dfrac{-1 \times \Big(\dfrac{1}{2a}\Big)}{x+a}+\dfrac{1 \times \Big(\dfrac{1}{2a}\Big)}{x-a}\Bigg)\,}dx$

In this mathematical expression,the factor $\dfrac{1}{2a}$ is common and it can be taken out from them.

$=\,\,\,$ $\displaystyle \int{\dfrac{1}{2a}\Bigg(\dfrac{-1}{x+a}+\dfrac{1}{x-a}\Bigg)\,}dx$

$=\,\,\,$ $\displaystyle \dfrac{1}{2a} \int{\Bigg(\dfrac{-1}{x+a}+\dfrac{1}{x-a}\Bigg)\,}dx$

$=\,\,\,$ $\displaystyle \dfrac{1}{2a} \int{\Bigg(\dfrac{1}{x-a}-\dfrac{1}{x+a}\Bigg)\,}dx$

$=\,\,\,$ $\displaystyle \dfrac{1}{2a}\Bigg(\int{\dfrac{1}{x-a}\,}dx-\int{\dfrac{1}{x+a}\,}dx\Bigg)$

Take $y = x-a$ and differentiate the equation with respect to $x$.

$\implies$ $\dfrac{dy}{dx} \,=\, \dfrac{d}{dx}{\, (x-a)}$

$\implies$ $\dfrac{dy}{dx} \,=\, \dfrac{d}{dx}{\, (x)}-\dfrac{d}{dx}{\, (a)}$

$\implies$ $\dfrac{dy}{dx} \,=\, 1-0$

$\implies$ $\dfrac{dy}{dx} \,=\, 1$

$\implies$ $dy \,=\, 1 \times dx$

$\implies$ $dy \,=\, dx$

$\,\,\, \therefore \,\,\,\,\,\,$ $dx \,=\, dy$

Take $z = x+a$ and differentiate the equation with respect to $x$.

$\implies$ $\dfrac{dz}{dx} \,=\, \dfrac{d}{dx}{\, (x+a)}$

$\implies$ $\dfrac{dz}{dx} \,=\, \dfrac{d}{dx}{\, (x)}+\dfrac{d}{dx}{\, (a)}$

$\implies$ $\dfrac{dz}{dx} \,=\, 1+0$

$\implies$ $\dfrac{dz}{dx} \,=\, 1$

$\implies$ $dz \,=\, 1 \times dx$

$\implies$ $dz \,=\, dx$

$\,\,\, \therefore \,\,\,\,\,\,$ $dx \,=\, dz$

Now, transform the terms in the expression in terms of $y$ and $z$.

$\implies$ $\displaystyle \dfrac{1}{2a}\Bigg(\int{\dfrac{1}{x-a}\,}dx-\int{\dfrac{1}{x+a}\,}dx\Bigg)$ $\,=\,$ $\displaystyle \dfrac{1}{2a}\Bigg(\int{\dfrac{1}{y}\,}dy-\int{\dfrac{1}{z}\,}dz\Bigg)$

### Evaluate the integration of each function

Use the reciprocal rule of integration to evaluate integral of each multiplicative inverse of variable.

$= \,\,\,$ $\displaystyle \dfrac{1}{2a}\Bigg(\int{\dfrac{1}{y}\,}dy-\int{\dfrac{1}{z}\,}dz\Bigg)$

$= \,\,\,$ $\dfrac{1}{2a}\Big(\log_e{|y|}+c_1-\log_e{|z|}+c_2\Big)$

$= \,\,\,$ $\dfrac{1}{2a}\Big(\log_e{|y|}-\log_e{|z|}+(c_1+c_2)\Big)$

$= \,\,\,$ $\dfrac{1}{2a}\Big(\log_e{|y|}-\log_e{|z|}\Big)$ $+$ $\dfrac{1}{2a}(c_1+c_2)$

The difference of the logarithmic terms can be simplified by the quotient rule of logarithms.

$= \,\,\,$ $\dfrac{1}{2a}\Big(\log_e{\Bigg|\dfrac{y}{z}\Bigg|}\Big)$ $+$ $\dfrac{c_1+c_2}{2a}$

$= \,\,\,$ $\dfrac{1}{2a}\log_e{\Bigg|\dfrac{y}{z}\Bigg|}+c$

Actually, we have taken that $y = x-a$ and $z = x+a$ in the expression.

$= \,\,\,$ $\dfrac{1}{2a}\log_e{\Bigg|\dfrac{x-a}{x+a}\Bigg|}+c$

$\therefore \,\,\,$ $\displaystyle \int{\dfrac{1}{x^2-a^2}\,}dx \,=\, \dfrac{1}{2a}\ln{\Bigg|\dfrac{x-a}{x+a}\Bigg|}+c$

Email subscription
Math Doubts is a free math tutor for helping students to learn mathematics online from basics to advanced scientific level for teachers to improve their teaching skill and for researchers to share their research projects. Know more
Follow us on Social Media
###### Math Problems

Learn how to solve easy to difficult mathematics problems of all topics in various methods with step by step process and also maths questions for practising.

Learn more